Vernacular Infrastructure: a hidden cost in the economics of climate change and permafrost thaw in Alaska - Emma L. Verstraete; Alexandra J. Zachwieja (Sustainable Futures)
The effects of climate change on infrastructure are expected to cost Alaska between 3–5 billion dollars by 2100. However, these projections do not include the costs associated with unofficial or “vernacular” infrastructure such as community trails, ice roads, or subsistence structures- all of which are indispensable elements for many Alaskan communities. These communities are already disproportionately impacted by climate change, and the loss of these structures threatens their ability to maintain economic independence. We highlight community winter trail infrastructure in Alaska and the role it plays in statewide transportation systems, providing at minimum 4000 additional miles of roadways than traditional routes when weather conditions are favorable. Using conservative estimates, maintenance of these community winter trails will cost at minimum 20 million dollars per year, without accounting for the rapid acceleration of climate change in the state. We argue for the inclusion of vernacular infrastructure costs in future economic models to calculate the most accurate cost of climate change to Alaskan infrastructure.